2019
DOI: 10.15517/rbt.v67is5.38938
|View full text |Cite
|
Sign up to set email alerts
|

Polychaete assemblages in a tropical hypersaline coastal lagoon of the southeastern Gulf of Mexico during the rainy season

Abstract: Introduction: The Río Lagartos lagoon, located in the Ría Lagartos Biosphere Reserve, Yucatán, Gulf of Mexico, is a coastal hypersaline system ca. 80 km long (east-west). It comprises three basins: western (close to Río Lagartos fishermen village), middle (Las Coloradas) and eastern (close to El Cuyo fishermen village), that communicate through very narrow natural channels. Despite several studies have been performed on the vertebrate fauna, the aquatic invertebrates, and especially polychaetes, remain largely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 51 publications
(84 reference statements)
0
1
0
Order By: Relevance
“…Samples were obtained from 16 stations distributed along the lagoon, in the three main basins of the system: Río Lagartos basin to the mouth, in the west (stations: 3, 6, 9, 12, 15), Las Coloradas basin, in the middle (stations: 20, 21, 22, 23, 25) and El Cuyo basin to the head of the lagoon, in the east (stations: 27, 29, 30, 32, 35, 38) (Figure 1A; Table 1). Spatial distribution of the stations was based on previous studies of abiotic and biotic variables, which indicated that the three basins can be considered environmentally and biologically distinct (Ortegón-Aznar et al ., 2001; Valdes & Real, 2004; Vega-Cendejas & Hernández De Santillana, 2004; Peralta-Meixueiro & Vega-Cendejas, 2011; Dávila-Jiménez et al ., 2019). The lagoon was sampled during three periods that coincided with the end of the three seasons in the region: the rainy season (September/October 2017), the cool Nortes season (February 2018) and the warm, dry season (May 2018) (Table 1).…”
Section: Methodsmentioning
confidence: 99%
“…Samples were obtained from 16 stations distributed along the lagoon, in the three main basins of the system: Río Lagartos basin to the mouth, in the west (stations: 3, 6, 9, 12, 15), Las Coloradas basin, in the middle (stations: 20, 21, 22, 23, 25) and El Cuyo basin to the head of the lagoon, in the east (stations: 27, 29, 30, 32, 35, 38) (Figure 1A; Table 1). Spatial distribution of the stations was based on previous studies of abiotic and biotic variables, which indicated that the three basins can be considered environmentally and biologically distinct (Ortegón-Aznar et al ., 2001; Valdes & Real, 2004; Vega-Cendejas & Hernández De Santillana, 2004; Peralta-Meixueiro & Vega-Cendejas, 2011; Dávila-Jiménez et al ., 2019). The lagoon was sampled during three periods that coincided with the end of the three seasons in the region: the rainy season (September/October 2017), the cool Nortes season (February 2018) and the warm, dry season (May 2018) (Table 1).…”
Section: Methodsmentioning
confidence: 99%